AN STUDY ON UTILIZATION OF IMMUNIZATION SERVICES BY SLUM DWELLERS OF MUNICIPAL CORPORATION AREA OF REWA CITY IN MADHYA PRADESH - Dubey, D K; Singh, S; Kushwah, S S (Indian Journal of Community Health, 2013)
Background: Immunization plays an important role in reducing child mortality and morbidity. Children’s of the urban poor suffer accentuated vulnerability to illnesses, as outbreaks of vaccine preventable diseases are more common in urban slums. Objective: To assess the immunization coverage in the urban slums of Rewa City. Methodology: A cluster survey based on probability proportion to size advocated under multi-indicator cluster survey by World Health Organization was used. Result: With regard to vaccinations; it was found that coverage was the highest for DPT-1 and OPV-1 (88.5%) and the lowest for measles vaccine (66.6%). Only 99 (47.1%) children had received Vitamin A at the time of measles vaccination. The coverage rate for all the vaccines was slightly higher among males as compared to females. Fully immunized children’s were 60.7 % and immunization coverage for individual vaccine was found to be more among the males as compared to females though the difference was found to be statistically insignificant. Conclusion: The study reflects low immunization coverage and non-utilization of measles vaccination and Vitamin A supplementation by slum dweller beneficiaries.